Education Through Wikipedia - Mkrtchyan, Susanna M. (Mathematical Problems of Computer Science, 2021)
Wikipedia belongs to education in various ways. One gains knowledge by reading Wikipedia, the other obtains profound knowledge by contributing to Wikipedia. It is the reason why educators in many countries include Wikipedia editing into their curriculum. The article is dedicated to the ecosystem of education through Wikipedia and other Wiki projects which were created by the author, developed by Wikimedia Armenia and settled in Armenia. For seven years Wikimedia Armenia has been implementing Wikipedia Educational projects in different rural regions of Armenia and hopefully will continue its development. The system offers permanent creative learning for teachers, as well as deep and interdisciplinary education on their future field of engagement with students. It revolutionarily changes the attitude of teachers and students towards education. It facilitates the teacher and student relationships. It also changes students’ interrelation from contest to cooperation. It shifts the attention of educational players from marks to topics’ perception. Of course, the most valuable advantage of this approach is that teachers improve their knowledge continuously and students, even not the smart ones gain comprehensive knowledge. This ecosystem is constantly improved based on statistical surveys. The components of the ecosystem were honored as the coolest Wikimedia projects and registered as trademarks: Wikicamp, Wikiclub. In the current article the full overview of education through wiki projects is given. The detailed description and innovative solutions on the challenges of today’s education will be introduced in the upcoming articles of the publication issue.